PENERAPAN PROGRAM CONSCIOUSNESS BASED EDUCATION UNTUK MEMBENTUK KARAKTER SISWA DI SMA NEGERI BALI MANDARA - Ardani, Ni Nengah Juni; Yudana, I Made; Sujana, I Putu Windu Mertha (Program Studi PPKn Universitas Pendidikan Ganesha, 2026)
The purpose of this study is to determine the results of the implementation of the Consciousness-Based Education Program in shaping the character of students at SMA Negeri Bali Mandara, analyze the factors that support and hinder the implementation of the CBE Program in shaping the character of students at SMA Negeri Bali Mandara, and describe alternative solutions designed to overcome various obstacles in the implementation of the CBE Program, so as to strengthen the positive impact and minimize the negative impact on the formation of student character at SMA Negeri Bali Mandara. This study employed a qualitative descriptive method, with data collection techniques including observation, interviews, and documentation. The qualitative data analysis process employed the analysis techniques according to Miles and Hubermen, namely data collection, data reduction, presentation, and conclusions. The results of this study indicate that the Consciousness-Based Education Program has been implemented since 2012. To support the success of this program, several activities are implemented, including Transcendental Meditation and Physical Fitness, which have been successfully implemented to date in shaping the character of students, particularly in grade 10 at SMAN Bali Mandara. Furthermore, the Consciousness-Based Education Program, supported by school commitment, adequate facilities, and intensive mentoring, faces obstacles such as initial student adaptation, limited concentration, and a busy schedule. To address these obstacles, alternative solutions have been designed and implemented, including initial orientation, schedule restructuring, and strengthened mentoring. These have been proven to increase the effectiveness of character development in grade 10 students at SMAN Bali Mandara. This research is expected to provide practical contributions for educational institutions, particularly boarding schools, in implementing the Consciousness-Based Education (CBE) program to strengthen the development of students’ discipline and responsibility character.